Generalization of Psychosocial Skills to Life Skills in Collegiate Athletes - Yuki Yabunaka; Ryo Kametani; Hironobu Tsuchiya (MDPI AG, 2023)
This study investigated how needs-supportive and needs-thwarting coaching behaviors, basic need satisfaction (BNS), and basic need frustration (BNF) are positively or negatively related to collegiate athletes' generalization of psychosocial skills in competitive sports. Japanese collegiate athletes (N = 228, Mage = 19.7 years) completed the measures to assess the study variables. Structural equation modeling for the hypothesized models of associations among the variables showed that needs-supportive coaching behavior positively influenced BNS, which, in turn, positively affected the generalization of all 10 psychosocial skills in competitive sports. Moreover, needs-thwarting coaching behavior had a positive influence on BNF, which, in turn, negatively affected the following skills: generalization of stress management, appreciating others, communication, and maintaining etiquette and manners. These findings highlight that coaches and life skills educational supporters should display needs-supportive behaviors that help to improve participants' BNS and promote generalization of the psychosocial skills for life skills development through competitive sports. Furthermore, they should prevent needs-thwarting behaviors that frustrate their basic needs in competitive sports.